Analisis Kepuasan Learning Management System Universitas XYZ Menggunakan Metode System Usability Scale dan K-Means - Irfani, Muhammad Haviz; Sartika, Dewi (UNIVERSITAS INDO GLOBAL MANDIRI, 2023)
The importance of knowing the results of using the LMS (Learning Management System) learning application to determine the overall use value of users each semester. User perceptions were obtained using the SUS (system usability scale) method using a questionnaire that adopted 10 questions distributed to 118 users (students) of the XYZ University Informatics Engineering study program who had used the LMS after 1 semester. The purpose of this study is to determine user perceptions by clustering user satisfaction which has been carried out for 1 semester. Grouping perceptions using the K-Means method with variables (columns) that seem to have the greatest influence on other variables. Other tools use Google Colab in the Python programming language. The number of variables is 10 variables adopted from the questions in the System Usability Scale method. The results of this study provide a total of 3 (three) clusters which will then become the basis for scoring the criteria for the SUS method. The criteria for using the LMS system with cluster 2 have an excellent rating (SUS score of 72.04) and the number of perceptions is 49 people from 118 students. Overall, LMS users provide good value for several modules in the LMS, but the third cluster with the highest number gives the best results from the other clusters.